2023
DOI: 10.1039/d3ay00155e
|View full text |Cite
|
Sign up to set email alerts
|

A fast survey on recent developments in designing colorimetric and fluorescent sensors for the selective detection of essential amino acids

Abstract: Owing to the biological significance of various amino acids, developing accurate and cost-effective sensing techniques for selective detection of amino acids has been growing interest in the current research field....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Amino acid digestion and utilization are closely related to shrimp culture [ 28 ]. Essential amino acids (EAAs), as they cannot be synthesized by humans, must be obtained from the regular diet [ 29 ]. Studies have shown that leucine increased the content of muscle crude protein, increased the number and area of hepatopancreas fiber cells, and improved the growth performance of P. vannamei [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid digestion and utilization are closely related to shrimp culture [ 28 ]. Essential amino acids (EAAs), as they cannot be synthesized by humans, must be obtained from the regular diet [ 29 ]. Studies have shown that leucine increased the content of muscle crude protein, increased the number and area of hepatopancreas fiber cells, and improved the growth performance of P. vannamei [ 30 ].…”
Section: Introductionmentioning
confidence: 99%